American Federalism in Practice : The Formulation and Implementation of Contemporary Health Policy - Doonan, Michael (Michael T.) (Book collections on Project MUSE., 2013)
American Federalism in Practice is a major contribution to our understanding of contemporary health policy in America. Always an important topic, the issue holds special currency today given the prominence of health care in today's political and economic landscape. Michael Doonan provides a unique perspective on American federalism and U.S. health policy in explaining how intergovernmental relations shape public policy in health as well as other critical areas. Doonan tracks federal-state relations through the creation, formulation, and implementation of three of the most important health policy initiatives since the Great Society: the Children's Health Insurance Program (CHIP) and the Health Insurance Portability and Accountability Act (HIPAA), both developed in Congress, and the Massachusetts health care reform program as it was developed and implemented under federal government waiver authority. Massachusetts, though not without having to face challenges, actually succeeded in lowering its uninsured rate to below two percent. Success and failure of these three programs can be traced in large part to a balance between state flexibility and accountability to meet program goals. Achieving that balance is not easy, of course, but lessons learned from previous successes --and failures --in structuring intergovernmental relations offer unique insights into national health reform and contemporary public policy. Doonan reveals how federalism can shift as the sausage of public policy is made, providing a previously missing link between federalism theory and practice. His work should change the way people think about federalism in a policy context while providing a new and useful framework through which we can view, and hopefully comprehend, some of the most important and polarizing policy debates of our time.